Commentary: Iconoclastic Reflections on the ‘Safety’ of Polyunsaturated Fatty Acid-Rich Culinary Frying Oils: Some Cautions regarding the Laboratory Analysis and Dietary Ingestion of Lipid Oxidation Product Toxins - Martin Grootveld; Benita C. Percival; Sarah Moumtaz; Miles Gibson; Katy Woodason; Azeem Akhtar; Michael Wawire; Mark Edgar; Kerry L. Grootveld (Applied Sciences, 2021)
Continuous or frequent ingestion of fried foods containing cytotoxic/mutagenic/genotoxic lipid oxidation products (LOPs) may present significant human health risks; such toxins are generated in thermally stressed polyunsaturated fatty acid (PUFA)-rich culinary frying oils (CFOs) during standard frying practices. Since monounsaturated and saturated fatty acids (MUFAs and SFAs, respectively) are much less susceptible to peroxidation than PUFAs, in this study CFOs of differential unsaturated fatty acid contents were exposed to laboratory-simulated shallow-frying episodes (LSSFEs). Firstly, we present a case study exploring the time-dependent generation of aldehydic LOPs in CFO products undergoing LSSFEs, which was then used to evaluate the relative potential health risks posed by them, and also to provide suitable recommendations concerning their safety when used for frying purposes. Sunflower, rapeseed, extra-virgin olive and coconut oils underwent LSSFEs at 180 °C: Samples were collected at 0–90 min time-points (n = 6 replicates per oil). Aldehydes therein were determined by high-resolution 1H NMR analysis at 400 and 600 MHz operating frequencies. For one of the first times, CFO LOP analysis was also performed on a non-stationary 60 MHz benchtop NMR spectrometer. 1H NMR analysis confirmed the thermally promoted, time-dependent production of a wide range of aldehydic LOPs in CFOs. As expected, the highest levels of these toxins were produced in PUFA-rich sunflower oil, with lower concentrations formed in MUFA-rich canola and extra-virgin olive oils; in view of its very high SFA content, only very low levels of selected aldehyde classes were generated in coconut oil during LSSFEs. Secondly, 1H NMR results acquired are discussed with regard to the suitability and validity of alternative, albeit routinely employed, spectrophotometric methods for evaluating the peroxidation status of CFOs and lipid-containing foods. Thirdly, an updated mini-review of the toxicological properties of and intake limits for LOPs, and deleterious health effects posed by their ingestion, is provided. In conclusion, exposure of PUFA-rich CFOs to high-temperature frying practices generates very high concentrations of aldehydic LOP toxins from thermally promoted, O2-powered, recycling peroxidation processes; these toxins penetrate into and hence are ‘carried’ by fried foods available for human consumption. Such toxins have the capacity to contribute towards the development and progression of non-communicable chronic diseases (NCDs) if cumulatively ingested by humans.